The Role of the Article in the Semantic Interpretation of the Antecedent in Attributive Clauses - Hayrapetyan, Nune (Armenian Folia Anglistika, 2013)
The role of the article in all grammar structures leaves no doubt. Attributive clauses prove no exception. Here, the article used with the antecedent contributes to the distinction of the attributive clause. Attributive clauses can be divisible and non-divisible. The antecedent of the latter is closely connected to the thematic continuation which acts as its characterization and does not need any restriction in the use of the article, i.e. both definite and indefinite article may be used here. Unlike non-divisible sentences, the antecedent in divisible attributive clauses is not strongly bound with its subordinate continuation since the latter contains additional information only. The semantic emphasis of the antecedent requires the use of only the definite article which can be used in zero category as an antecedent used in the presence of proper nouns.